The Vulnerability of Sub-Saharan Africa to Financial Crises: the Case of Trade - (:unkn) unknown (My University, 2012)
Motivated by the 2008–09 financial crisis and the trade collapse, the paper analyzes the effect of past banking crises (1976–2002) on trade with a focus on African exporters. The paper shows that they are particularly vulnerable to a banking crisis in the countries they export to. It also distinguishes between an income effect (during a banking crisis, income and exports to the country fall) and a disruption effect (a banking crisis disrupts the financing of trade channels). For the average country, the disruption effect is moderate (a deviation from the gravity predicted trade of between 1 and 5 percent). The paper finds however that the disruption effect is much larger and long-lasting for African exporters as the fall in trade (relative to gravity) is 10 to 15 percentage points higher than for other countries in the aftermath of a banking crisis. This vulnerability of African exports in the short run does not come from a composition effect, that is, from the fact that primary exports are disrupted more severely than manufacturing exports. Instead, the paper provides suggestive evidence that the dependence of African countries upon trade finance is an important determinant of their vulnerability to banking crises in partner countries.
Keywords: African Research